Pediatric Logistic Organ Dysfunction 2 Scoring System in Predicting the Prognosis of Death in Pediatric Patients with Clinical Sepsis - Rahwanda Surya; Sindu Saksono (Sriwijaya Journal of Surgery, 2019)
ABSTRACT Introduction. Sepsis is still one of the main causes of mortality and morbidity in children in industrialized and developing countries. Pediatric Logistic Organ Dysfunction 2 (PELOD 2) score aims to assess the degree of organ system disorder. In addition, PELOD score 2 also has a close relationship with death and can detect any organ dysfunction even in patients with low mortality. This study aims to determine the relationship between PELOD 2 score with the death of patients in pediatric surgical cases with clinical sepsis at Dr. Mohammad Hoesin Hospital (RSMH) Palembang. Methods. An observational analytic study with a cohort design was conducted at the Mohammad Hoesin Hospital in Palembang from August 2017 to December 2017. There were 30 samples of pediatric patients with clinical sepsis who met the inclusion criteria. Data frequency and distribution are explained in tabular form. The relationship between PELOD 2 score (Pediatric Logistic Organ Dysfunction 2) with death was analyzed by the Fisher Exact test. Survival rates are obtained by analyzing survival using Kaplan meier. Data analysis uses SPSS version 18.0. Results. In this study, the results showed that there were no differences in age, weight, height and sex between groups with mortality and life outcomes (p> 0.05). With the Fisher Exact test, it was found that there was a significant relationship between PELOD 2 score and mortality in pediatric patients with clinical sepsis (RR = 13; RR> 2; p = 0.000; p> 0.05). Of 30 pediatric patients with clinical sepsis, there were 13 deaths (43.3%) of pediatric patients with clinical sepsis where 13 out of 15 people (86.7%) in the risk group and the comparison group did not get any deaths. Conclusions. It can be concluded that there is a significant relationship between PELOD 2 score (Pediatric Logistic Organ Dysfunction 2) with the death of patients in pediatric surgical cases with clinical sepsis at Dr. Mohammad Hoesin Hospital (RSMH) Palembang.